NATO Science Series
DOI: 10.1007/1-4020-3252-8_8
|View full text |Cite
|
Sign up to set email alerts
|

Humic Acids as Barriers in Actinide Migration in the Environment

Abstract: Humic acids (HAs) and fulvic acids (FAs) are the main components of natural waters that can influence the migration ability of cations. They form stable complex compounds with actinide elements that can change their solubility. In addition, HAs could be responsible for migration of colloidal species. The role of HAs in formation of geochemical barriers in actinide migration in the geosphere is discussed on the basis of results of laboratory experiments and speciation of plutonium and neptunium in field samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Kalmykov et al (2005) found that HA binding dominated the migration behavior of aquatic radionuclides, especially actinides, and in manners that depended on the actinide. In bottom sediments of the Ynisey River (Russia), for example, plutonium was mostly associated with the humin and mineral components of the sediments, whereas americium was bound to mobile FA or other low‐molecular‐weight organic substances.…”
Section: Humic Substances In Natural Waters Vary With Environmental Fmentioning
confidence: 98%
“…Kalmykov et al (2005) found that HA binding dominated the migration behavior of aquatic radionuclides, especially actinides, and in manners that depended on the actinide. In bottom sediments of the Ynisey River (Russia), for example, plutonium was mostly associated with the humin and mineral components of the sediments, whereas americium was bound to mobile FA or other low‐molecular‐weight organic substances.…”
Section: Humic Substances In Natural Waters Vary With Environmental Fmentioning
confidence: 98%